2021
DOI: 10.1186/s40359-021-00692-6
|View full text |Cite
|
Sign up to set email alerts
|

Promoting psycho-social wellbeing for engaging inflammatory bowel disease patients in their care: an Italian consensus statement

Abstract: Background Inflammatory bowel diseases (IBD) are remitting and relapsing diseases that mainly interest the gastrointestinal tract. IBD is associated with a condition of psycho-social discomfort that deeply compromises the quality of life and the competence of patient to be fully engaged in their self-management. As a consequence, effective care of IBD patients should include not only medical but also psychological support in order to improve patients' wellbeing. Although this, to date there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 110 publications
(91 reference statements)
0
16
0
Order By: Relevance
“…This implies that individuals actively engaged in managing their health may perceive fewer limitations or disruptions in their daily lives stemming from food-related issues and tend to have improved psychological well-being, potentially due to better coping strategies or adaptive behaviors. Similarly, higher levels of quality of life have been linked with higher health engagement among individuals with IBD [ 33 , 54 ]. In addition, individuals with the lowest food-related quality of life levels were classified into the “Hedonist” cluster, and their high food involvement may have contributed to increased cravings.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that individuals actively engaged in managing their health may perceive fewer limitations or disruptions in their daily lives stemming from food-related issues and tend to have improved psychological well-being, potentially due to better coping strategies or adaptive behaviors. Similarly, higher levels of quality of life have been linked with higher health engagement among individuals with IBD [ 33 , 54 ]. In addition, individuals with the lowest food-related quality of life levels were classified into the “Hedonist” cluster, and their high food involvement may have contributed to increased cravings.…”
Section: Discussionmentioning
confidence: 99%
“…Co-existing mental health issues are also prevalent within the paediatric population and impact on their quality of life and compliance with treatment. 79 Graffigna et al 80 highlighted the importance of early identification and management of mental health issues in patients to ensure optimal patient engagement. Adequate medication education and training is paramount to increase compliance and limit side effects.…”
Section: Mdt Managementmentioning
confidence: 99%
“…Of the professions listed above, the role of a dedicated IBD psychologist seems to be the most debated one, and is often not even considered as an extended member of the MDT 101. However, as the importance of the brain-gut axis and the effect of psychological symptoms on IBD management are increasingly being recognised,80 a more recent Italian consensus statement identified psychological support as an essential component in holistic IBD care model 110. Although more evidence is needed, a prospective pilot study offering this type of integrated psychological support, not only found improvements in IBD symptoms, and psychological well-being, but also reductions in outpatient appointments and imaging 111.…”
Section: Role Of the Mdt In The Holistic Care Modelmentioning
confidence: 99%